Proteomic Profiling Reveals a Specific Role for Translesion DNA Polymerase η in the Alternative Lengthening of Telomeres - Garcia-Exposito, Laura; Bournique, Elodie; Bergoglio, Valérie; Bose, Arindam; Barroso-Gonzalez, Jonathan; Zhang, Sufang; Roncaioli, Justin L.; Lee, Marietta; Wallace, Callen T.; Watkins, Simon C.; Opresko, Patricia L.; Hoffmann, Jean-Sébastien; et al. (Cell reports (Cambridge), 2016)
Cancer cells rely on the activation of telomerase or the alternative lengthening of telomeres (ALT) pathways for telomere maintenance and survival. ALT involves homologous recombination (HR)-dependent exchange and/or HR-associated synthesis of telomeric DNA. Utilizing proximity-dependent biotinylation (BioID), we sought to determine the proteome of telomeres in cancer cells that employ these distinct telomere elongation mechanisms. Our analysis reveals that multiple DNA repair networks converge at ALT telomeres. These include the specialized translesion DNA synthesis (TLS) proteins FANCJ-RAD18-PCNA and, most notably, DNA polymerase eta (Polη). We observe that the depletion of Polη leads to increased ALT activity and late DNA polymerase δ (Polδ)-dependent synthesis of telomeric DNA in mitosis. We propose that Polη fulfills an important role in managing replicative stress at ALT telomeres, maintaining telomere recombination at tolerable levels and stimulating DNA synthesis by Polδ. [Display omitted] •Utilize BioID to profile the composition of telomeres in cancer cells•DNA polymerase eta (Polη) localizes specifically to ALT telomeres•Loss of Polη enhances ALT and promotes mitotic DNA synthesis at telomeres Garcia-Exposito et al. use BioID to determine the composition of telomeres in human cancer cells that rely on distinct telomere elongation mechanisms to survive. They suggest that the translesion polymerase DNA polymerase eta (Polη) regulates the recombination-associated alternative lengthening of telomeres (ALT) mechanism.